Cross-Border Integration and Development in the CAN and the MERCOSUR: Macroregional approaches for Cross-Border Territorial Planning - Wong Villanueva, José Luis (Revista Española de Desarrollo y Cooperación, 2022)
This article aims to analyze the role of the instruments for the territorial planning and zoning of cross-border areas in the CAN and MERCOSUR. Considering as case studies the Border Integration Zones (ZIFs) and the Linked Border Localities (LFVs) respectively, they are evaluated based on their formulation, implementation, and impact. The analysis reveals that the exchange of experiences, the consideration of new territorial configurations, and a greater study of the spatial configurations of policies would be beneficial for cross-border integration and development processes.
Keywords: territorial planning; cross-border integration; cross-border regions; CAN; MERCOSUR